Learning management systems and the realities of using open source software - Philip Roy (Flexible Learning Association of New Zealand, 2012)
Open source software has gained prominence thanks to the Internet and the ability to establish communities, share ideas, and distribute software. It embraces the academic ideals of cooperation and knowledge sharing, as well as being seen to have a low Total Cost of Ownership, greater flexibility, and adaptability. However, many projects have been created from funding that sees their success dependent upon financial support, while the voluntary nature of developer involvement means projects are susceptible to internal politics. Those contemplating an open source Learning Management System should look at its history, community, and technical requirements, as well as reflect upon the stability of commercial software alternatives.